SYSTEMATIC LITERATURE REVIEW: THE EFFECTIVITY OF ARTICULATE STORYLINE MEDIA TO IMPROVING CRITICAL THINKING SKILLS - Akhlilia, Tudrika; Novita Puspa Dewi; Sri Wardani; Nuni Widiarti (Institut Pendidikan Indonesia, 2024)
ABSTRACT Various challenges occur in the era of globalisation with advances in technology and information, so it is necessary to develop IPAS learning media that can improve students' critical thinking skills. Realistic and conceptual IPAS learning media will make it easier for students to understand the subject matter. This research aims to explore literature studies related to the use of Articulate Storyline learning media on students' critical thinking skills in IPAS subjects in elementary schools. This research uses the SLR (Systematic Literature Review) method. This research collected data by collecting 20 accredited national and international journal articles on the utilisation of articulate storyline learning media from 2020 to 2024. These articles were obtained from Google Scholar, Research Gate, SINTA, and DOAJ. This research shows that Articulate Storyline 3 learning media can improve students' critical thinking skills. Kata Kunci : Learning Media, Articulate Storyline, Critical Thinking